2014
DOI: 10.2308/accr-50971
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CEO Power on Compensation Contract Design

Abstract: We investigate whether CEO power influences a firm's decision to change its compensation system in response to regulatory and public pressure. In particular, we assess whether CEO power influences the choice of performance measures as a form of camouflage to minimize the impact of these reforms on their wealth. We examine one component of CEO pay, namely, the use of performance-vested stock option (PVSO) plans, and find that firms with powerful CEOs attach less challenging targets in the initial PVSOs granted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 90 publications
10
125
0
6
Order By: Relevance
“…Nonetheless, some inconsistencies remain. Specifically, recent evidence suggests that powerful CEOs are able to influence their compensation arrangements (Abernethy et al., ; Morse et al., ). For example, using US data for the period 1992–2003, Morse et al.…”
Section: Relevant Literature and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, some inconsistencies remain. Specifically, recent evidence suggests that powerful CEOs are able to influence their compensation arrangements (Abernethy et al., ; Morse et al., ). For example, using US data for the period 1992–2003, Morse et al.…”
Section: Relevant Literature and Hypotheses Developmentmentioning
confidence: 99%
“…In response, many companies attempt to justify large compensation packages by offering performance‐based pay in the form of equity grants and options. However, the performance targets used in these contracts may offer an avenue for firms to camouflage higher pay (e.g., Abernethy et al., ). While the literature is informative about the strategic use of stock and option grants, we argue that cash bonuses may be used as another means to camouflage high levels of executive pay.…”
Section: Introductionmentioning
confidence: 99%
“…efficiency = β0 + β1CEOPower + β2Age + β3lev + β4roa + ε (2) In equation (2), efficiency is explained variable, representing investment efficiency. CEOPower is explanatory variable, representing CEO power.…”
Section: Model Buildingmentioning
confidence: 99%
“…Abernethy, Margaret etc. (2015) studied the CEO power effect on the adjustment of the compensation system, the study showed that company's powerful CEO is more inclined to adopt more easily in the pay system to complete the performance targets [2]. Zhong-xin wu and Yan sisi (2016) has carried on the empirical research of the relationship d between CEO power and enterprise performance, research shows CEO power influence mechanism of enterprise performance [3].…”
Section: Ceo Powermentioning
confidence: 99%
“…In looking at US CEOs, Abernethy, Kuang and Qin (2015) find evidence that powerful CEOs can influence the adoption and choice of performance-vested stock options, which can negate the benefit of these forms of remuneration to shareholders. Qu, Percy, Stewart and Hu (2016) conduct a similar study in the Australian setting and also find that long tenured CEOs appear to influence the granting of stock options with less restrictive vesting conditions such as shorter vesting periods and options without performance hurdles attached.…”
Section: Optimal Contracting and Managerial Power Theorymentioning
confidence: 99%